Implementasi Metode Montessori Dalam Berbagai Bidang Studi: Pengenalan dan Pelatihan Metode Montessori Bagi Guru dan Tenaga Kependidikan di SD Muhammadiyah Pahandut Palangka Raya - Dwi Sari Usop; Rospala Hanisah Yukti Sari; Isnaeni Marhani; Istiqamah Hafid (JPM: Jurnal Pengabdian Masyarakat, 2021)
The 2019 coronavirus (Covid-19) pandemic in Indonesia has decreased. Some schools have started holding face-to-face meetings with students. Some schools are still doing distance learning (online). Many problems are found in online learning, such as the lack of attention of students and lack of understanding of students understanding the material presented by the teacher. Therefore, it is necessary to use learning methods that can attract the interest and attention of students in distance learning (online). One of the learning methods is the Montessori method. The use of the Montessori method is considered to be able to provide a different atmosphere for students in the learning process. In fact, there are still teachers in schools who are not familiar with the Montessori method The use of the Montessori method is considered to be able to provide a different atmosphere for students in the learning process. In fact, there are still teachers in schools who are not familiar with the Montessori method so that they need to be introduced and given special training so that knowledge insights are developed and can be practiced during daily learning